2006
DOI: 10.1073/pnas.0510928103
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs direct rapid deadenylation of mRNA

Abstract: MicroRNAs (miRNAs) are ubiquitous regulators of eukaryotic gene expression. In addition to repressing translation, miRNAs can down-regulate the concentration of mRNAs that contain elements to which they are imperfectly complementary. Using miR-125b and let-7 as representative miRNAs, we show that in mammalian cells this reduction in message abundance is a consequence of accelerated deadenylation, which leads to rapid mRNA decay. The ability of miRNAs to expedite poly(A) removal does not result from decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
787
1
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,003 publications
(830 citation statements)
references
References 32 publications
31
787
1
11
Order By: Relevance
“…In fact, miRNA-binding can clearly destabilize target mRNA by a mechanism distinct from the Argonaute-catalysed sequence specific cleavage that characterize RNAi (Bagga et al, 2005;Farh et al, 2005;Lim et al, 2005;Giraldez et al, 2006). Detailed analyses of miRNA-directed mRNA decay revealed that miRNAs induce translation-independent deadenylation of the targeted mRNA, which is the hallmark of deadenylation-dependent decapping followed by 5 0 -to-3 0 decay (Giraldez et al, 2006;Wu et al, 2006). Remarkably, AU-rich elements (ARE) in the 3 0 UTRs of unstable mRNAs can also accelerate the shortening of the poly(A) tail triggering decapping and RNA destruction, and there are hints of connections between the miRNA and ARE pathways.…”
Section: Mechanism(s) Of Mirna-mediated Gene Regulationmentioning
confidence: 99%
“…In fact, miRNA-binding can clearly destabilize target mRNA by a mechanism distinct from the Argonaute-catalysed sequence specific cleavage that characterize RNAi (Bagga et al, 2005;Farh et al, 2005;Lim et al, 2005;Giraldez et al, 2006). Detailed analyses of miRNA-directed mRNA decay revealed that miRNAs induce translation-independent deadenylation of the targeted mRNA, which is the hallmark of deadenylation-dependent decapping followed by 5 0 -to-3 0 decay (Giraldez et al, 2006;Wu et al, 2006). Remarkably, AU-rich elements (ARE) in the 3 0 UTRs of unstable mRNAs can also accelerate the shortening of the poly(A) tail triggering decapping and RNA destruction, and there are hints of connections between the miRNA and ARE pathways.…”
Section: Mechanism(s) Of Mirna-mediated Gene Regulationmentioning
confidence: 99%
“…Recent studies have shown that miRNAs can regulate expression of their target genes by decreasing mRNA stability, in addition to translational inhibition (Yekta et al, 2004;Bagga et al, 2005;Wu et al, 2006). The strategy to identify target genes of miR-512-5p is shown in Figure 4a.…”
Section: Epigenetic Activation Of Mir-512-5pmentioning
confidence: 99%
“…In addition to the slicer activity, miRNA can accelerate the target mRNA deadenylation and decapping thus affecting the translation initiation and transcript stability [28]. Translation is also indirectly regulated by spatial separation of miRNA-targeted mRNA complex from translational machinery into the cytoplasmic P-bodies, also known as processing bodies [29].…”
Section: Effector Stagementioning
confidence: 99%